PRELIMINARY PHYTOCHEMICAL SCREENING OF CAMELLIA SINENSIS & TINOSPORA CORDIFOLIA USED IN TRADITIONAL MEDICINE - ANUBRATA PAUL; ARPANA VIBHUTI; SAMUEL RAJ (International Journal of Pharma and Bio Sciences, 2016)
Preliminary screening of phytochemicals is a valuable step, in the detection of the bioactive principles present in medicinal plants and subsequently may lead to drug discovery and development. In the present study, chief phytoconstituents of the two selected medicinal were identified in order to relate their presence with bioactivities of the plants. Screening of two selected medicinal plants (Camellia sinensis & Tinospora cordifolia) was performed for the presence of tannins, flavonoids, terpenoids, steroids, glycosides, alkaloids and phenolic compounds using standard methods. The selected medicinal plants were found to contain tannins, flavonoids, phenolic compounds, terpenoids, glycosides, alkaloids in different extracts of methanol, diethyl ether, isoamyl alcohol, water, butan1-ol, ethyl acetate in Camellia sinensis and Tinospora cordifolia. Moreover, flavonoids were also present in water and methanol extracts of Tinospora cordifolia and Camellia sinensis. On the other hand, alkaloids and steroids were present in the water, isoamyl alcohol, methanol extracts of Camellia sinensis and Tinospora cordifolia. In addition, tannins, glycosides and phenols were present in diethyl ether, butan1-ol, water extracts of Camellia sinensis and Tinospora cordifolia. It is evident from the study that Camellia sinensis & Tinospora cordifolia have the highest therapeutic efficacy possessing majority of phytochemical classes of compounds.